Encouraging Eco-Entrepreneurship: The Impact of University Entrepreneurial Support on Developing Students’ Green Entrepreneurial Intentions in Skikda University - Benkhaoua, Rayene; Messikh, Ayoub (Naše gospodarstvo/Our economy, 2025)
This study examines the effect of university support mechanisms on students’ green entrepreneurial intentions at Université 20 Août 1955, Skikda. The research methodically assesses how educational initiatives, institutional policies, and physical infrastructure shape students’ commitment to developing environmentally responsible ventures. Descriptive and analytical survey methods are systematically applied to investigate these relationships. The results indicate that university support significantly enhances students’ green entrepreneurial intentions. These findings highlight the importance of integrating sustainability into entrepreneurship education and institutional strategies. Nonetheless, the research is limited by its focus on a single university and reliance on self-reported data, which may affect the generalizability of results. This study addresses a gap in Arabic academic literature by examining institutional support as a central factor in sustainable entrepreneurship. The findings indicate that universities and policymakers should enhance entrepreneurial ecosystems to promote green entrepreneurship and strengthen graduates’ contributions to sustainable development.
Keywords: University entrepreneurial support; Entrepreneurial intention; Green entrepreneurship; Skikda